Telemonitoring is Acceptable Amongst Community Dwelling Older Australians with Chronic Conditions: A Literature Review - Yuana Dwi Agustin (D'Nursing and Health Journal (DNHJ), 2020)
Introduction: Chronic disease is a serious health problem and the leading cause of death in the world. In 2008, chronic disease caused the death of 36 million people worldwide, or the equivalent of 36% of the world's deaths. Chronic conditions accounted for about 9 out of every 10 deaths in Australia in 2015. Method: This study used pretest and posttest methods for telemonitoring intervention in the elderly with chronic conditions. The method of using telemonitoring was explained by the researcher before the research was carried out, this is evident by 20 respondents out of 21 respondents who stated that the explanation of computer use was easy to understand, and more than half of the respondents stated that the computerized system in telemonitoring was easy to use. Result: The results of the research in this journal article explain that more than half of the research respondents would recommend using telemonitoring every day to their family and friends. This proves that the use of telemonitoring can be accepted by the elderly in Australia. Conclusion: chronic disease conditions experienced by the elderly can be prevented by using telemonitoring which can help evaluate the health conditions of the elderly without having home visits, because nurses will know the condition of the elderly/patients who are at home every day.